Potential of Sriwijaya Thermal Cycler Smart Controlling-Based as a Tool for DNA Sequence Polymerase Chain Reaction - Msy Rulan Adnindya; Indri Seta Septadina; Muhammad Reagan (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Introduction. Along with the COVID-19 pandemic, the need for a thermal cyclerdevice for examining COVID-19 is getting bigger. Many laboratories have overusedthe use of thermal cyclers due to the limited availability of this tool. This study aimsto test the effectiveness of the Sriwijaya thermal cycler based on a smart controllerin conducting PCR DNA sequences. Methods. The research design was anexperimental study with a posttest control group approach, in order to see anoverview of the results of the polymerase chain reaction (PCR) in the form ofintermediate DNA bands using Sriwijaya Thermal Cycler compared to groups usingfactory-made Thermal cyclers. Results. The PCR results showed precise results fromthe image and band separation, and there was a clear separation of the bands onthe marker. The PCR results from the ACE I / D gene showed quite good and optimalresults in the separation of the PCR results band. Conclusion. Sriwijaya thermalcycler is effective in DNA polymerase chain reaction (PCR) sequences comparable tothat of the manufacturer's Thermal Cycler.